Accoglienza dei migranti e turismo sostenibile nelle Alpi. Il ruolo dell'impresa sociale - Membretti, Andrea; Galera, Giulia (Antropologia Pubblica, 2017)
The authors analyze the link between two distinct phenomena that are increasingly related in Italian Alpine localities: tourism development and foreign immigration. Special attention is paid to asylum seekers, who have gradually started to repopulate mountain localities, following the policy decision to distribute migrants across the whole national territory. After an introductory analysis, the article focuses on two good practices of welcome initiatives that, while experimenting innovative social inclusion strategies in the tourism domain, have managed to overcome the emergency rationale that inspires most reception policies. Thanks to their embeddedness in local communities, the selected organizations have restored mountain trails, revitalized mountain agriculture through innovative crops and committed to the promotion of a welcome culture through sensitization activities. Based on the good practices investigated, the authors’ hypothesis is that some of the “forced highlanders” could become “highlinders by choice”, contributing to the survival and the sustainability of the tourism system, put at risk by the population decline and ageing of local inhabitants. Adequate policies are however needed to fulfil this hypothesis on a wider scale and to pave the way for the transformation of welcome initiatives into development opportunities for receiving communities. Welcome policies should reject the logic of placing large numbers of recipients in abandoned barracks and residences and the selection and financing mechanisms of managing entities should be redefined so as to select managing organizations that are rooted at the local level and draw on the participation of different stakeholders of the receiving community in their governing bodies.